2013
DOI: 10.1186/1532-429x-15-84
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between cardiovascular magnetic resonance and Doppler echocardiography in the measurement of transvalvular gradient in aortic stenosis: the effect of flow vorticity

Abstract: BackgroundValve effective orifice area EOA and transvalvular mean pressure gradient (MPG) are the most frequently used parameters to assess aortic stenosis (AS) severity. However, MPG measured by cardiovascular magnetic resonance (CMR) may differ from the one measured by transthoracic Doppler-echocardiography (TTE). The objectives of this study were: 1) to identify the factors responsible for the MPG measurement discrepancies by CMR versus TTE in AS patients; 2) to investigate the effect of flow vorticity on A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 38 publications
0
37
0
Order By: Relevance
“…The VENC PC sequence is an established and non-invasive tool used to quantify the velocity and blood flow based on the accumulated phase of moving protons [14,15]. Previous studies have manually assessed AVA on cine sequences and used in-house or customized software to assess hemodynamic parameters from a VENC PC sequence in valvular stenosis [3,8,[16][17][18]. We only used VENC PC sequences and commercial software for easy access in daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The VENC PC sequence is an established and non-invasive tool used to quantify the velocity and blood flow based on the accumulated phase of moving protons [14,15]. Previous studies have manually assessed AVA on cine sequences and used in-house or customized software to assess hemodynamic parameters from a VENC PC sequence in valvular stenosis [3,8,[16][17][18]. We only used VENC PC sequences and commercial software for easy access in daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The tendency to underestimate was apparent in severe AS due to intravoxel dephasing signal loss related in part to acceleration, alignment of the image plane with the jet, flow turbulence, partial volume effect, background noise, and phase wrap [3,5,9,[19][20][21][22]. Caruthers et al [14] reported that the VENC PC sequence underestimated velocity-time integral in more than half of patients with an AVA less than 0.8 mm 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 In fact, flow vorticity has been determined as one of the main factors responsible for discrepancies in terms of aortic transvalvular pressure gradients between CMR and echocardiography. 9 In addition to vortical structures, 10 4D-flow magnetic resonance imaging allows quantifying the eccentricity of the flow, 11 which can be calculated as the normalized flow displacement. 1 The loss of mechanical energy caused by the perturbations of the aortic blood flow as a result of vorticity and eccentricity might lead to a significant increase of the left ventricular afterload, 12 hence offering a possible explanation for the observed association between flow displacement and left ventricular hypertrophy in the study from von Knobelsdorff-Brenkenhoff et al 1 Indeed, the energy loss index, 13 which is dependent on the size relationship between the stenotic aortic valve orifice and the aorta, 12 provides additional prognostic value in the evaluation of patients with asymptomatic aortic stenosis.…”
Section: Aortic Blood Flow Patterns In Aortic Stenosismentioning
confidence: 99%